Enhanced performance of green mortar comprising high volume of ceramic waste in aggressive environments. (10th July 2019) - Mohammadhosseini, Hossein; Lim, Nor Hasanah Abdul Shukor; Tahir, Mahmood Md.; Alyousef, Rayed; Alabduljabbar, Hisham; Samadi, Mostafa
Highlights: Ceramic waste was used in the production of sustainable mortar. Mortar with ceramic waste exhibited better compressive strength. Ceramic waste notably improved mortar resistance against aggressive environments. The utilisation of ceramic waste in mortar has both technical and environmental benefits. Abstract: Different types of waste materials generated from various industries require proper and sufficient management to assure a clean environment. The application of solid waste in sustainable construction has attracted much attention due to its potential properties, decreased cost and saving land space that would otherwise be used for landfill purposes. In this study, the long-term performance of mortar comprising ceramic waste powder as supplementary cementing material and ceramic particles as fine aggregates, which were exposed to chloride and sulphate attack, was investigated. The effect of the ceramic waste was also assessed using scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analysis. Results of this study indicated that the utilisation of ceramic waste in both forms of binder and fine aggregates significantly improved the long-term compressive strength of the mortar and provided higher resistance against aggressive environments. The positive interaction amongst the ceramic waste powder and fine aggregates enabled higher crystalline formation, and therefore, reduction in porosity and cracks. In addition, it also prevented the mortar spalling from being exposed to chloride and sulphate attacks. Based on the results, it was concluded that the utilisation of ceramic waste in the production of sustainable mortar that is exposed to aggressive environments is technically and environmentally feasible.